An assessment of Social Media marketing’s influence on Brand Loyalty, through the Moderating role of Brand Reputation - Muhammad Sibt e Ali (Journal of Peace, Development and Communication, 2023)
The study’s core theme is SMM’s (Social Media Marketing) role in the development of brand loyalty through the moderating role of brand reputation on brand trust and loyalty. Subsequently, about 550 buyers of various online retailers focusing on electronics, apparel and cosmetics social media platforms in Pakistan were surveyed using a standardized survey form and the random sample approach to obtain information. The primary factors of the research were SMM, Electronic word of mouth, brand commitments, brand trust, brand reputation, social media rewards, and brand loyalty. The proposed framework under this study extracts the empirical stats using SPSS, like demographics, reliability, descriptive statistics, and correlation. Confirmatory Factor Analysis assessed the accuracy and preciseness of the model and SEM-Structured Equation Model technique applied to the suggested model using SmartPLS 4. The findings indicate that social media marketing, electronic word of mouth and social media rewards positively impact brand trust and loyalty to the firms. The connection involving brand trust and brand loyalty is favored by brand reputation. Brand commitment and brand trust significantly influence brand loyalty. Our understanding of how social media marketing might impact brand commitment and trust, which in turn can affect brand loyalty, is improved by this work. The paper’s conclusion discusses limitations and potential long-term effects.